Targeted monetary policy, dual rates and bank risk taking - Francesca Barbiero; Lorenzo Burlon; Maria Dimou; Jan Toczynski (European Central Bank (ECB), 2022)
We assess whether central bank credit operations influence the size and composition of bank credit in a negative interest rate environment. We exploit confidential information from the newly established European credit registry to capture bank lending conditions and bank risk-taking. For identification, we use high-frequency reactions of bank bonds around the announcement of the April 2020 recalibration of the ECB's Targeted Longer-Term Refinancing Operations (TLTROs). We find that the credit easing measures had a strong positive effect on bank credit, even when controlling for possible confounding factors. The increase in lending was not accompanied by excessive risk-taking, especially for banks with low intermediation margin, that is, those that were poised to benefit the most from TLTROs' borrowing rates below the interest rates on central bank reserves.
Keywords: E51; E52; G01; G21; 330; unconventional monetary policy; bank lending; risk-taking; dual rates